Investigative errors: concept and their essence (Journal of actual problems of jurisprudence, 2019)
The author considers the defi nition of investigative errors and their essence. Improving the activity of the preliminary investigationis a necessary condition to ensure the inevitability of criminal punishment. At the same time, the strengthening of the rule of law, therights and freedoms of the individual in the exercise of criminal proceedings, are becoming increasingly important.Keywords: investigation, crime, punishment, the activities of the preliminary investigation, the justice.